(untitled) (Journal of Economic Research & Business Administration, 2015)
The interrelationship between 111 variables for 144 countries was studied by method of principal components. Two principal components were chosen from twelve components that were received from the decomposition of initial data. The analysis of these components illustrates that «Institutes», «Business», and «Innovation» pillars are key factors for competitiveness improvement. Unfortunately, these pillars are poorly developed in Kazakhstan. It is necessarily to pay special attention to these pillars in order to improve the position of Kazakhstan in the world economic forum’s rating.